2018
DOI: 10.3389/fmicb.2018.02951
|View full text |Cite
|
Sign up to set email alerts
|

Campylobacter coli From Retail Liver and Meat Products Is More Aerotolerant Than Campylobacter jejuni

Abstract: Aerotolerance in the microaerophilic species Campylobacter was previously reported and could increase bacterial survival and transmission in foods during stressful processing and storage conditions. In this study, 167 Campylobacter isolates (76 C. jejuni and 91 C. coli) were screened for aerotolerance; these strains were previously isolated from retail chicken meat, chicken livers, chicken gizzards, turkey, pork, and beef liver samples. Bacterial cultures were incubated aerobically in Mueller Hinton broth with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 45 publications
3
28
3
1
Order By: Relevance
“…C. jejuni was shown to survive longer in liver juice 45 . Aerotolerant C. jejuni strains were identified 46 but also aerotolerant C. coli isolates were highly prevalent in other studies 47 . Survival in harsh environments might be a result of various factors and also dependent on the specific genomic background.…”
Section: Discussionmentioning
confidence: 68%
“…C. jejuni was shown to survive longer in liver juice 45 . Aerotolerant C. jejuni strains were identified 46 but also aerotolerant C. coli isolates were highly prevalent in other studies 47 . Survival in harsh environments might be a result of various factors and also dependent on the specific genomic background.…”
Section: Discussionmentioning
confidence: 68%
“…Several reports have shown that some strains of C. jejuni are aerotolerant and may survive efficiently under aerobic conditions 24,30,40) , suggesting that aerotolerant strains may pose an increased risk in terms of food contamination and human infection. According to a study from Canada, approximately 36% of C. jejuni isolates from retail chicken meat are highly tolerant to aerobic conditions 30) and C. jejuni strains with increased aerotolerance survive longer on chicken meat than those sensitive to aerobic conditions 41) .…”
Section: Characteristics Of C Jejuni/colimentioning
confidence: 99%
“…Food products containing chicken liver, including pâté, parfait, and mousse, were identified as sources of human campylobacter outbreaks ( Merritt et al., 2011 , Farmer et al., 2012 , Parry et al., 2012 , Centers for Disease Control and Prevention, 2013 , Edwards et al., 2014 , Scott et al., 2015 , Glashower et al., 2017 ). Of human concern, C. jejuni or Campylobacter coli have been isolated from chicken livers ( Barot et al., 1983 , Khalafalla, 1990 , Boukraa et al., 1991 , Wieliczko, 1994 , Baumgartner et al., 1995 , Fernandez and Pison, 1996 , Cox et al., 2006a , Cox et al., 2007 , Cox et al., 2009 , Strachan et al., 2012 , Harrison et al., 2013 , Firlieyanti et al., 2016 , McLauchlin et al., 2017 , Karki et al., 2018 ). Recent culinary trends, especially intentional undercooking of liver, may explain the increase of chicken liver products responsible for human campylobacteriosis.…”
Section: Introductionmentioning
confidence: 99%
“…Campylobacter may adapt to liver parenchyma to better survive in refrigerated poultry products, and affect its transmission to humans. Some strains of C. coli isolated from chicken livers are hyper-aerotolerant, more so than C. jejuni strains isolated from chicken livers ( Karki et al., 2018 ). Incubation of Campylobacter with retail chicken liver juice supports biofilm formation in C. coli and the survival of C. jejuni at 4°C ( Karki et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%